Bombs, IEDs and explosives identification, investigation, and disposal techniques - Laska, Paul R. (CRC Press/Taylor & Francis Group, 2016)
This book stresses the need for flexibility and creativity in response. Bombs, IEDs, and Explosives provides a ready reference on a wide variety of technical, administrative, and legal information that makes it indispensable to bomb disposal professionals and units.